PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS TEORI BRUNER BERMUATAN KARAKTER UNTUK SEKOLAH DASAR - Supriyono; Rintis Rizkia Pangestika (Jurnal Gentala Pendidikan Dasar, 2021)
The aims of this research are to: produce mathematics teaching materials based on Bruner's Theory containing appropriate characters for elementary schools. The research method used is the ADDIE Research and Development model, which consists of five stages, namely analysis, planning, development, implementation, and evaluation. The population in this study was the fifth grade students of SD N Ngupasan, totaling 30 students. Data collection techniques used are interviews and questionnaires. The analytical technique used is descriptive and quantitative statistics. The results of this study indicate that product validation data by learning device experts is obtained in the "Eligible" category. Validation analysis data by material experts was obtained in the "Eligible" category. Therefore, it can be concluded that the product of Bruner's theory-based Mathematics learning device containing character is appropriate for use for elementary school students.